Dimensions of reading: a study of the beliefs of language and literature preservice teachers - González Ramírez, Carolina; Pescara Vásquez, Enzo (Frontiers in Psychology, 2023)
This study aims to analyze the beliefs that future Language and Literature teachers hold regarding reading. This work is part of a broader research endeavor focused on the reading habits and practices of teachers in training and their role as prospective mediators since the way in which they perceive reading significantly impacts the mediation processes they undertake in their teaching practices to cultivate readers. To achieve these objectives, a multiple case study is conducted, involving interviews with 1st-year students (n=15), 3rd-year students (n=15), and 5th-year students (n=15) enrolled in Language Pedagogy programs across three universities affiliated with the Chilean Council of Rectors. For data analysis, a content analysis approach is employed, supported by NVivo 12. The findings reveal that beliefs about reading primarily fall into two dimensions: academic and personal, with the former exhibiting clearer definition and characterization. This can be attributed to the influence of the disciplines integrated into their education, namely literature and linguistics. In conclusion, it is imperative to address the social dimension of reading during the initial teacher education program, as this aspect is not emphasized by preservice teachers, despite its pivotal role in shaping their identity as reading mediators within the context of their teaching practice.